The Implementation of Local Wisdom-Based Vocational Hospitality Curriculum Development Model - Polii, Bernadain Dainty; Permana, Dimas Ero (AIBPM Publisher, 2021)
Vocational higher education has a strategic role and is at the forefront in handling the age of the workforce and educating them into skilled, professional, and highly competitive persons who will enhance the nation's competitiveness. This study aims to formulate a design model for the development of a vocational hospitality curriculum based on local wisdom for students of the Tourism Department. The vocational curriculum development model will be highly useful for determining measures or policies to improve the quality of human resources hospitality industry fields. The research method used is research and development, which includes a descriptive method, action research, and experimentation. This curriculum development model emphasizes the development of broader methods of not only how to teach but also how to build students’ character.